Clinical and pathological characterization of ophthalmic disease in a canine model of mucopolysaccharidosis type I. Issue 2 (16th January 2023) - Nenninger, Ariel; Ben‐Shlomo, Gil; Allbaugh, Rachel; Valentine, Bethann; Snella, Elizabeth; Jens, Jackie; Ellinwood, N. Matthew; Smith, Jodi
Abstract: Mucopolysaccharidosis type I (MPS I) is a rare lysosomal storage disease caused by α‐L‐iduronidase enzyme deficiency, resulting in glycosaminoglycan (GAG) accumulation in various cell types, including ocular tissues. Ocular manifestations in humans are common with significant pathological changes including corneal opacification, retinopathy, optic nerve swelling and atrophy, and glaucoma. Available treatments for MPS I are suboptimal and there is limited to no effect in treating the ocular disease. The goal of this study was to characterize the clinical and pathological features of ocular disease in a line of MPS I affected dogs, including changes not previously reported. A total of 22 dogs were studied; 12 MPS I were affected and 10 were unaffected. A subset of each underwent complete ophthalmic examination including slit lamp biomicroscopy, indirect ophthalmoscopy, rebound tonometry, and ultrasonic pachymetry. Globes were evaluated microscopically for morphological changes and GAG accumulation. Clinical corneal abnormalities in affected dogs included edema, neovascularization, fibrosis, and marked stromal thickening. Intraocular pressures were within reference interval for affected and unaffected dogs. Microscopically, vacuolated cells containing alcian blue positive inclusions were detected within the corneal stroma, iris, ciliary body, sclera, and optic nerve meninges of affected dogs. Ganglioside accumulation was identified by luxol fast blue staining in rare retinal ganglion cells. Increased lysosomal integral membrane protein‐2 expression was demonstrated within the retina of affected animals when compared to unaffected controls. Results of this study further characterize ocular pathology in the canine model of MPS I and provide foundational data for future therapeutic efficacy studies.